Neutralizing Antibody Levels and Epidemiological Characteristics of Patients with Breakthrough COVID-19 Infection in Toyama, Japan - Tani, Hideki; Inasaki, Noriko; Yazawa, Shunsuke; Shimada, Takahisa; Saga, Yumiko; Kaya, Hiroyasu; Maruyama, Yumiko; Matano, Sadaya; Itoh, Hiroyuki; Kashii, Tatsuhiko; Yamazaki, Emiko; Itamochi, Masae; et al. (Japanese Journal of Infectious Diseases, 2023)
Breakthrough infection (BI) after coronavirus disease 2019 (COVID-19) vaccination has increased owing to the emergence of novel SARS-CoV-2 variants. In this study, we analyzed the epidemiological information and possession status of neutralizing antibodies in patients with BI using SARS-CoV-2 pseudotyped viruses. Analysis of 44 specimens from patients diagnosed with COVID-19 after two or more vaccinations showed high inhibition of infection by 90% or more against the Wuhan strain and the Alpha and Delta variants of pseudotyped viruses in 40 specimens. In contrast, almost no neutralizing activity was observed against the Omicron BA.1 variant. Many patients without neutralizing activity or BI were immunosuppressed. The results of this study show that contact with an infected person can result in BI, even when there are sufficient neutralizing antibodies in the blood. Thus, sufficient precautions must be taken to prevent infection even after vaccination.